Effect of tubal recanalization on functional and fertility outcomes in previously sterilized women: A prospective study - A, Rathna; Sharma, Nidhi (Journal of Neonatal Surgery, 2025)
Background: Tubal recanalization has emerged as an important fertility-restoring procedure for women seeking reversal of sterilization. While previous studies have examined surgical outcomes, comprehensive data on functional and fertility outcomes remain limited. This study aimed to evaluate the success rates, fertility outcomes, and psychosocial impact of tubal recanalization in a contemporary surgical setting. Methods: A prospective cohort study was conducted at saveetha medical college over three years, enrolling 215 women aged 20-45 years who underwent laparoscopic tubal recanalization. Participants were selected based on strict criteria including residual tubal length ≥4cm and normal ovarian reserve. Surgical outcomes, conception rates, pregnancy outcomes, and psychological parameters were systematically evaluated through standardized protocols and validated questionnaires during 24 months of follow-up. Results: The procedure achieved 86.5% surgical success with 76.3% natural conception rates among successful cases. Mean time to conception was 8.4 months, with live birth, miscarriage, and ectopic pregnancy rates of 76.1%, 15.5%, and 8.4% respectively. Significant improvements were observed in anxiety/depression scores and fertility-related quality of life. Multivariate analysis identified age <35 years, residual tubal length ≥5cm, and interval since sterilization <7 years as significant predictors of success. Conclusions: Tubal recanalization demonstrates high efficacy in restoring fertility with favourable pregnancy outcomes when performed in appropriately selected patients. The procedure offers substantial psychological benefits and represents a valuable option for women seeking fertility restoration after Sterilization. These findings support its role in contemporary reproductive care while highlighting important considerations for patient selection and counselling.